Management of atherosclerosis risk factors for patients at high cardiovascular risk in real-world practice: a multicentre study - Arintaya Phrommintikul (2018)
© 2017, Singapore Medical Association. All rights reserved. INTRODUCTION Atherosclerotic cardiovascular disease is a global health burden. However, there are heterogeneities among countries or regions in the risk factors and clinical manifestations of atherosclerotic diseases as well as management patterns. METHODS We collected data from 25 centres in Thailand. Patients with documented coronary artery disease, cerebrovascular disease or peripheral arterial disease, or with at least three atherosclerosis risk factors were enrolled between April 2011 and March 2014. Data on demographics, atherosclerosis risk factors and the management pattern of risk factors, including laboratory findings, were recorded. RESULTS In total, 9,390 patients, including 4,861 patients with established atherosclerotic disease and 4,529 patients with multiple risk factors, were enrolled. The modifiable risk factors, other than current smoking habit (5.3%), were common: hypertension (83.8%), dyslipidaemia (85.9%) and diabetes mellitus (57.4%). A majority of patients with hypertension (96.3%), dyslipidaemia (93.8%) and diabetes mellitus (78.5%) received medications for their conditions. Antiplatelet agents were given to 73.9% of patients. The undertreatment rate of cardiovascular risk factors, such as blood pressure, low-density lipoprotein cholesterol, haemoglobin A1c and smoking status, was 35.8%, 59.0%, 45.3% and 5.3%, respectively. CONCLUSION Conventional atherosclerosis risk factors were common among Thai patients with established atherosclerotic disease. Even though most of the patients received recommended treatments according to established guidelines, a significant proportion of them were undertreated for atherosclerosis risk factors.